Relatório de estágio técnico profissional em medicina veterinária: clínica, cirurgia, nutrição, reprodução e sanidade de ruminantes - Silva, Crístian Perosa da (2023)
The Supervised Professional Technical Internship (ETPS) is an opportunity to improve and put into practice all the theoretical knowledge acquired during the Veterinary Medicine degree, in the area intended for professional practice. The ETPS was carried out in the area of ​​Clinic, Surgery, Nutrition, Reproduction and Health of Ruminants, under the academic guidance of Prof. Dr. Maria Isabel Botelho Vieira. The ETPS was carried out at Fazenda Santo Isidoro/Stedile Pecuária de Leite, from July 10th to November 3rd, 2023, totaling 510 hours. Through ETPS, it was possible to experience the routine within a high-productivity farm, assisting the veterinarian in clinical, surgical, reproductive, nutritional, health and milk quality care. Therefore, this report includes a description of the internship location, the general activities carried out and the conditions monitored during this period, presented in table format for a better understanding. The supervised professional technical internship was fundamental for professional and personal maturity, through the opportunity to experience dairy farming. Get to know the routine of a veterinarian on a farm, interact with different people, as well as follow specialized sectors and professionals in order to enrich the academic's vision of the future of the profession as a veterinarian. Finally, a case of Abomasus Displacement to the left will be reported.